2012
DOI: 10.1155/2012/430176
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Mitochondrial Alterations and Increased Oxidative Stress in Nutritional Diabetes-PronePsammomys obesusModel

Abstract: Mitochondrial dysfunction is considered to be a pivotal component of insulin resistance and associated metabolic diseases. Psammomys obesus is a relevant model of nutritional diabetes since these adult animals exhibit a state of insulin resistance when fed a standard laboratory chow, hypercaloric for them as compared to their natural food. In this context, alterations in bioenergetics were studied. Using liver mitochondria isolated from these rats fed such a diet for 18 weeks, oxygen consumption rates, activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…The threshold for this biphasic effect appears in part to be dependent on the oxidant buffering capacity of the cell, as decreases in glutathione levels appear to lower the threshold for stress-induced damage within the cell (28,78,88,89). GSH, an oxidant scavenger, is depleted by diabetes across different tissues and models of diabetes (5,27,34,61,106,107,123). Consistent with those reports we observed significant decreases in GSH as an early change that preceded increases in mitochondrial ROS or mtDNA damage.…”
Section: Discussionsupporting
confidence: 88%
“…The threshold for this biphasic effect appears in part to be dependent on the oxidant buffering capacity of the cell, as decreases in glutathione levels appear to lower the threshold for stress-induced damage within the cell (28,78,88,89). GSH, an oxidant scavenger, is depleted by diabetes across different tissues and models of diabetes (5,27,34,61,106,107,123). Consistent with those reports we observed significant decreases in GSH as an early change that preceded increases in mitochondrial ROS or mtDNA damage.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the treatment with avocado oil abolished both the exacerbation in ROS production and the inhibition of the complex I activity observed in diabetic rats, which further supports the hypothesis that complex I was the solely site of ROS production in these animals. Diabetes also decreases NADH dehydrogenase and complex I activity in liver mitochondria from alloxan-treated rats (Lukivskaya et al 2007) and diabetic, obese, Psammomys obesus gerbils (Bouderba et al 2012), respectively, further suggesting that complex I is an important target in the liver of diabetic models. However, our data of ETC complex activities in diabetic rats seems to be in conflict with some reports about this topic.…”
Section: Discussionmentioning
confidence: 96%
“…The issue about the duration of treatment with STZ and the effects on ETC function was addressed by other study (Satav and Katyare 2004), where it was found that respiration with complex I and complex II-linked substrates was inhibited at the end of 1-month STZ treatment, but longer times were not tested. Moreover, the diabetes-prone Psammomys obesus gerbil, a rodent model of nutritional diabetes, displayed an inhibition in the activity of the complexes I and III and upregulation of complex II activity after 18 weeks of feeding with a hypercaloric diet (Bouderba et al 2012). From this report and our results, it seems that after several weeks of hyperglycemia (~8-12, according to the report of Raza et al 2011 and our results), complex II is upregulated probably to increase the flux of electrons towards ETC to compensate an eventual decrease in electron transfer at complex I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They comprise mitochondrial membrane potential and proton leak kinetics, assessment of mitochondrial content by ultrastructural observations, citrate synthase activity and ratio of mitochondrial relative to nuclear DNA, polarographic determination of oxygen consumption rates, enzyme activities of mitochondrial respiratory complexes I-V, markers of oxidative stress such as mitochondrial production of superoxide anion and lipid peroxidation products, and anti-oxidant capacity such as superoxide dismutase specific activity and reduced to oxidized glutathione ratio (Bouderba et al, 2012;García-Ruiz et al, 1995;Pérez-Carreras et al, 2003;Raffaella et al, 2008;Vendemiale et al, 2001;Vial et al, 2011).…”
Section: In Vitro Methodsmentioning
confidence: 99%